Surgical removal of a large vaginal calculus formed after a tension-free vaginal tape procedure. Issue 11 (November 2016) - Zilberlicht, Ariel; Feiner, Benjamin; Haya, Nir; Auslender, Ron; Abramov, Yoram
Abstract Vaginal calculus is a rare disorder which has been reported in association with urethral diverticulum, urogenital sinus anomaly, bladder exstrophy and the tension-free vaginal tape (TVT) procedure. We report a 42-year-old woman who presented with persistent, intractable urinary tract infection (UTI) following a TVT procedure. Cystoscopy demonstrated an eroded tape with the formation of a bladder calculus, and the patient underwent laser cystolithotripsy and cystoscopic resection of the tape. Following this procedure, her UTI completely resolved and she remained asymptomatic for several years. Seven years later she presented with a solid vaginal mass. Pelvic examination followed by transvaginal ultrasonography and magnetic resonance imaging demonstrated a large vaginal calculus located at the lower third of the anterior vaginal wall adjacent to the bladder neck. This video presents the transvaginal excision and removal of the vaginal calculus.